The Sociopragmatic Perspective of Typographical Features in Students’ SMS and Whatsapp Text Messages - Ifan Iskandar (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
This study aims to examine the typographical features of English and Indonesian languages in students’ text messages delivered to the lecturers and the sociopragmatic perspective of the features collected from respondents of diverse profession and education backgrounds. Content analysis is employed to conduct the study whose data are the typographical features identified in 1,521 students’ SMS and that of in 527 WhatsApp text messages and followed by a survey of sociopragmatic attitudes towards the features gathered from 223 respondents. The findings recognize the typographical features of emoticons, vowel deletion, letter deletion, rebus writings—letter deletion, number deletion, letter-number deletion, and images or symbols—and phonetic spelling. The features are employed in various approaches as identified in the ways letters are deleted in the initial, medial and final syllables of the words. Social factor and dimension analyses underpinning the sociopragmatic perspective of the features suggests that the students communicate with older participants in written mode about serious matters for informative function and that the students and lecturers are socially distant between subordinate to superior with high formality degree for referential function which is high information content and low affective content. This social factor and dimension implies the use of formal style which is in line with the respondents’ attitudes acknowledging the formal employment of the language in text messaging.  Sociopragmatically, the typographical features are supposed to be used only when texting to the equally aged or younger participants, to the participants who are socially equal or lower with no distance, and for social communication functions or topics, not professional ones